Financial Attitude, Locus of Control, and Social Environment on the Financial Management Behavior of Housewives - Cerya, Efni; Desparatni, Teni (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2025)
This study investigates the impact of financial attitudes, locus of control, and social environment on financial management behavior among housewives in Pasaman Regency. Employing a quantitative approach with a descriptive method, the research adopts a causative design to establish causal relationships between variables. The population comprises housewives in Pasaman Regency, and the sample was selected using probability sampling with a random sampling technique. Slovin’s formula determined the sample size, yielding 100 respondents. Data collection was conducted through structured questionnaires, and the data were analyzed using multiple linear regression. The results indicate that financial attitudes have a significant influence on financial management behavior. In addition, locus of control also significantly affects financial management behavior. The next finding shows that the social environment significantly impacts financial management behavior. This study discloses that financial attitudes, locus of control, and social environment collectively have a significant and positive influence on financial management behavior. These findings provide practical insights and guidelines for improving financial management practices among housewives. Keywords: locus of control, financial management, social environment, financial attitude